Adaptive capacity of ski resorts in Western Norway to projected changes in snow conditions. Issue 22 (17th November 2021) - Dannevig, Halvor; Gildestad, Ida M.; Steiger, Robert; Scott, Daniel
ABSTRACT: Skiing is an important part of Norwegian culture, but as climate change leads to warmer, more variable winters, the ski industry needs to adapt. Despite the growing literature on climate change impacts on ski tourism, adaptation options, particularly beyond snowmaking, barriers and the financial and visitor experience implications remain under-researched. Employing projections for future snow and snowmaking conditions, this paper investigates adaptive capacity among seven Western Norwegian ski resorts. Adaptive capacity is examined in terms of physical situation, technology, economic resources, innovative ability, networks and institutions. We find that smaller resorts make up for poor economic performance by drawing on local community support and by implementing innovative efforts to diversify income. Nonetheless, despite high adaptive capacity with respect to networks, institutions and innovative ability, increased snow production costs will make operations in three low-lying resorts unviable as early as the 2030s, with salient implications for winter tourism patterns, small community economies and future participation in the sport. The results also suggest that studies using snow production model projections that represents physical and technical adaptive capacity only, may be conservative in their estimated impact of future climate change.